Oral erythema multiforme: Laboratory findings in monitoring Herpes simplex virus involvement (A case report) - Raiyon, Maria Leny; Subita, Gus Permana (Padjadjaran Journal of Dentistry, 2008)
Erythema Multiforme is polymorphous recurrent eruptions on the skin and oral mucosa. This case is describing a progression of a case of Erythema Multiforme in the oral mucosa of a 33-year-old man suggesting of herpes viral involvement. In the absence of identified inducing drugs, past medical history of clinical manifestation on Herpes Simplex Viral (HSV) but positive serum antibody against HSV-1 is suggesting of Herpes Associated Erythema Multiforme. This became the basis of the patient management. Several episodes of recurrences and relapses occurred during our treatment period in oral isolated sites which were later progressed with skin eruption of bullae. The later clinical presentation challenges the on going working diagnosis. It also necessitated a skin biopsy to rule out another possibility of bullous lesion diseases. The latter blood test showed seroconverted of HSV-2 antibody accompanying previous detected HSV-1 antibody. Both biopsy and peripheral blood sera test consistent with Herpes Simplex Virus involvement. The patient is on a scheduled antiviral prophylaxis. This case showed that Herpes Associated Erythema Multiforme (HAEM) does present initially as an isolated oral lesions and a serological test could be used to monitor seroconverting of HSV.